Competitive Strategy And Performance Of Quantity Surveying Firms In Malaysia - Abidin, Nazirah Zainul; Adros, Nur Azila; Hassan, Hasnanywati (Penerbit Universiti Sains Malaysia, 2014)
The competitiveness of the construction industry is affected by the number of new entrants, the strength of rivals, clients' expectations and a firm's own resources. However, the country's economic situation also affects the stability of the industry, and thus its competitive strength. This research focuses on the adoption of competitive strategies within quantity surveying (QS) firms of varying sizes during a period of economic fluctuation in Malaysia. The success of any strategy adopted is determined by the performance of the firm. Through a survey, this study revealed that firm size did not have a major impact on the choice of competitive strategy during this economic situation. The QS firms preferred differentiation strategies, and growth strategies were less preferred. The firms created attractiveness in the services offered by expanding the range of services, improving reputation and securing existing clients. For small- and medium-sized firms, this strategy enabled them to achieve the highest business performance, a satisfactory number of clients, and for large-sized firms, the strategy provided positive improvement in the number of projects in hand.